Cell free DNA: A Novel Predictor of Neurological Outcome after Intravenous Thrombolysis and/or Mechanical Thrombectomy in Acute Ischemic Stroke Patients - Atulabh Vajpeyee; Teddy Wijatmiko; Manisha Vajpeyee; Onjal Taywade (Neurointervention, 2018)
Purpose Several blood markers have been evaluated in stroke patients, but their role remains limited in clinical practice. This study was designed to evaluate the utility of cell free DNA (cf DNA) in stroke patients undergoing therapeutic intervention in the form of mechanical thrombectomy in acute ischemic stroke patients. Materials and Methods Twenty-six patients with ischemic stroke who were managed with interventions like intravenous thrombolysis (IVT) and mechanical thrombectomy were recruited consecutively in this study. The cf DNA was extracted by using circulating nucleic acid kit and measured by real-time quantitative PCR assay for β-globin gene. The neurological outcome was measured by modified Rankin scale (mRS) score at three months after the onset of symptoms. Results Cf DNA levels correlated with severity of stroke at the time of admission (r=0.421, P=0.032) and poor outcome at three months (r=0.606, P=0.001). Therapeutic intervention in the form of mechanical thrombectomy or IVT was associated with improved outcome in patients with cf DNA <10,000 kilogenome-equivalents/L (P=<0.05). Conclusion Cf DNA level correlated well with the 3 month outcome in acute ischemic stroke patients. It can be a potential supplementary marker to predict neurological outcome after therapeutic intervention.